If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -23 = 29 + -3 Reorder the terms: -23 + 10x = 29 + -3 Combine like terms: 29 + -3 = 26 -23 + 10x = 26 Solving -23 + 10x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + 10x = 26 + 23 Combine like terms: -23 + 23 = 0 0 + 10x = 26 + 23 10x = 26 + 23 Combine like terms: 26 + 23 = 49 10x = 49 Divide each side by '10'. x = 4.9 Simplifying x = 4.9
| (3x-4y^2)(9x^2+12xy^2+16y^4)= | | -1=4x-(3x-9)+-(-2x+8) | | X^2+4y^3=36 | | -12x+1+3x=-80 | | 3y-6x=48 | | c=0.009x^3+30x+14.3 | | 2x-7=3y-1 | | 65+85x=320 | | 4x+x+24=180 | | a-5=14+3 | | 571+874-d=161 | | 12e+-8=-20 | | 4x+x+24=82 | | 2b+10=18 | | (X+4)-5=20 | | -3.8-13.4p=-464.406 | | 4x+x+24=80 | | 30x^2+29x-357=0 | | 6x-x=2.5 | | 20+4x=80 | | 4x+x+24=85 | | 8H-3H+2K= | | n-.17=.4 | | 4+20x=80 | | -5-9(1+7b)=25 | | 14+2x=20+150x | | 2(x-7)=5(x-2) | | 0.9+12x=0.14+5 | | 18-3p=30 | | 3(4x-5)=4(3x+2) | | 11/x-2=3/x | | 4y-x=-6 |